2021
DOI: 10.1038/s41598-021-92741-8
|View full text |Cite
|
Sign up to set email alerts
|

An increasing role of pyrethroid-resistant Anopheles funestus in malaria transmission in the Lake Zone, Tanzania

Abstract: Anopheles funestus is playing an increasing role in malaria transmission in parts of sub-Saharan Africa, where An. gambiae s.s. has been effectively controlled by long-lasting insecticidal nets. We investigated vector population bionomics, insecticide resistance and malaria transmission dynamics in 86 study clusters in North-West Tanzania. An. funestus s.l. represented 94.5% (4740/5016) of all vectors and was responsible for the majority of malaria transmission (96.5%), with a sporozoite rate of 3.4% and avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 85 publications
(84 reference statements)
2
46
0
Order By: Relevance
“…funestus) as a dominant malaria vector has been documented in many east and southern African countries [ 12 17 ]. In locations such as south-eastern Tanzania [ 12 , 18 ], and in some districts in northern Tanzania around Lake Victoria [ 19 ], this species is responsible for 85–97% of all malaria transmission events. In addition to having relatively high sporozoite prevalence and high vectorial capacity, An.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…funestus) as a dominant malaria vector has been documented in many east and southern African countries [ 12 17 ]. In locations such as south-eastern Tanzania [ 12 , 18 ], and in some districts in northern Tanzania around Lake Victoria [ 19 ], this species is responsible for 85–97% of all malaria transmission events. In addition to having relatively high sporozoite prevalence and high vectorial capacity, An.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having relatively high sporozoite prevalence and high vectorial capacity, An. funestus has also been shown to be highly resistant to insecticide [ 19 ], long survival [ 20 ], and more anthropophilic [ 21 ] than co-existing vector species in several settings. Consequently, An.…”
Section: Introductionmentioning
confidence: 99%
“…), Anopheles arabiensis and Anopheles gambiae s.s ., with An. gambiae s.s being the predominant species [ 18 ] .
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…However, a number of studies including work by Cohuet et al [ 22 ] and Mendis et al [ 23 ] on Anopheles funestus s.l. populations have identified varying degrees of seasonality, including population abundance peaking in the dry season [ 24 ]. Relatedly, a number of studies have shown Anopheles annularis s.l.…”
Section: Introductionmentioning
confidence: 99%